Synthesis of Bi1.5Pb0.5Sr2Ca2Cu3Oy via sol-gel method using different acetate-derived precursors - Halim, S.A.; Saleh, Al-Khawaldeh; Azhan, H.; Mohamed, S.B.; Khalid, K.; Suradi, J. (Kluwer Academic Publishers, 2000)
Sol-gel method have been used to convert metal carbonates, oxides and nitrates into corresponding acetate precursors for gel formation. About 90% volume of high Tc superconducting phase (2223) has been obtained for oxide-carbonate system. This value is comparable to that obtained from pure acetates (91% volume). However, the nitrates-'derived sample has a high-Tc phase of 88% due to poor conversion of nitrates to acetates as observed by the infrared spectra. The dominance of high-Tc phase was observed in all systems as evidenced in the single step transition of R-T curves. Hence the percentage of the high-Tc phase dictates the value of Tc(R=0) as 104 K, 103 K and 99 K, for oxide-carbonate, pure metal acetates and nitrates system respectively.